TRANSPARANSI PENGOLAAN BADAN USAHA MILIK DESA (BUMDes) DI DESA KAMANGA KECAMATAN TOMPASO - PAKAYA, NADYA; RORONG, ARIE; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2019)
BUMDes is a village-owned enterprise established on the basis of village needs and potential as an effort to improve community welfare. Transparency is needed in the management of this Village-Owned Business Entity. This study aims to find out how transparent the management of Village Owned Enterprises in Kamanga Village, Tompaso Subdistrict, both in terms of community recognition and response. This study uses a phenomenological approach by conducting interviews. The results of this study are the practice of transparent administration in the form of the availability of financial reports and other data concerning the transparency of management of BUMDes. This study used a qualitative research method. The data collection technique was carried out by interviewing, documenting, and collecting data with documents to see how Transparency in managing BUMDes Kalooran in Kamanga Village, Tompaso District. The researcher used four indicators namely Document Availability and Accessibility, Clarity and Completeness of Information, Process Openness, and Regulatory Framework that Guarantees Transparency. Based on the results of the research conducted, the BUMDes Kalooran was not transparent in its management, seen from the availability of documents not provided by the management, and the community that did not know about the BUMDes program. The government seems closed in processing and running the BUMDes program. It can be concluded that the management of the Owned Enterprise of Kalooran Village in Kamanga Village, Tompaso Subdistrict is not transparent in its management.Keywords: Transparency, Management, Business Entity, Village